Features of Development of Regional Economy and Macroeconomic Trends in the XXI Century - Myagkova, Yulia Y.; Zimovich, Lyudmila E.; Aleksakhina, Yuliya V.; Khaibullina, Irina V.; Nosova, Svetlana S.; Lyubimtseva, Svetlana V. (International Journal of Economics and Financial Issues, 2016)
Microeconomic approach is based on the fact that in the process of historical development in the world formed a certain system of countries which, thanks to its economic power and cultural potential, advances in scientific and technological progress, common understanding of international politics, especially international obligations on human rights and the functioning of democratic power structures and influences events in the world. So, by the end of the XX century, the world has formed a special region, including the UK, Italy, Russia, USA, Germany, France, Japan. Joint actions of these countries allow you to perform three functions: first, to contribute to their own development through active integration; second, to actively maintain relations of good neighborliness and peace; third, to provide various forms of material, financial and military assistance to countries that need it. The geopolitical approach is typical for some of the territorial unity of neighboring countries. In Europe, Asia, Latin America formed alliances of countries, which established the common market. There is a new economic integration of European countries by retaining only a symbolic border of the countries in the Union. Created a unified economic field with the common market, currency, rules of management. Keywords: macroeconomics, region, regional economy, development, trends JEL Classifications: E01, O11, O20, R11, R13